2020
DOI: 10.3390/ijerph17082796
|View full text |Cite
|
Sign up to set email alerts
|

Vigorous-Intensity Physical Activities Are Associated with High Brown Adipose Tissue Density in Humans

Abstract: Brown adipose tissue (BAT) plays a role in adaptive thermogenesis in response to cold environments and dietary intake via sympathetic nervous system (SNS) activation. It is unclear whether physical activity increases BAT density (BAT-d). Two-hundred ninety-eight participants (age: 41.2 ± 12.1 (mean ± standard deviation), height: 163.6 ± 8.3 cm, weight: 60.2 ± 11.0 kg, body mass index (BMI): 22.4 ± 3.0 kg/m2, body fat percentage: 25.4 ± 7.5%) without smoking habits were categorized based on their physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 80 publications
1
7
0
1
Order By: Relevance
“…It is in line with the results of previous studies that the increased expression of the UCP-1 thermogenic gene in obese non-diabetic adults after giving 70%-80% intensity exercise [46]. In their study, Tanaka et al [15] also concluded an increase in UCP-1 expression in adult men with average body mass index after moderate-intensity walking exercise [15]. Research using experimental animals with weight exercise also concluded that exercise increases the UCP-1 thermogenic gene [47], activity of thermogenic genes such as PGC-1α, UCP-1, as well as acid transport genes after moderate-intensity continuous exercise and high-intensity interval exercise [29].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…It is in line with the results of previous studies that the increased expression of the UCP-1 thermogenic gene in obese non-diabetic adults after giving 70%-80% intensity exercise [46]. In their study, Tanaka et al [15] also concluded an increase in UCP-1 expression in adult men with average body mass index after moderate-intensity walking exercise [15]. Research using experimental animals with weight exercise also concluded that exercise increases the UCP-1 thermogenic gene [47], activity of thermogenic genes such as PGC-1α, UCP-1, as well as acid transport genes after moderate-intensity continuous exercise and high-intensity interval exercise [29].…”
Section: Resultssupporting
confidence: 90%
“…Therefore, a non-pharmacological approach based on exercise is required. Exercise carries physiological effects that significantly affect the body [13], one of which it increases the expression of the thermogenesis gene [14] and activates the adipose network, decreasing lipid accumulation [15]. Therefore, the preparation of an exercise program as a non-pharmacological therapy for obese individuals through increasing activity of thermogenic genes is interesting to be developed further [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings showed a remarkable reduction in VAT in the high-intensity group exhibited, while no change was observed in the moderate group [ 67 ]. A recent study reported that vigorous-intensity physical activities are associated with high BAT density in humans, suggesting that long-term high-intensity physical activities might positively influence BAT content [ 68 ]. Collectively, the intensity of exercise training seems to play an essential role in changing adipose tissue.…”
Section: Exercise Strategies To Prevent Obesity and Improve Adipose Tissue Healthmentioning
confidence: 99%